CEGAH PENULARAN PENYAKIT HEPATITIS B PADA IBU HAMIL MELALUI PENINGKATAN PENGETAHUAN, DETEKSI DINI DAN PHBS DI WILAYAH PUSKESMAS SUNGAI TABUK I KABUPATEN BANJAR - Norsiah, Wahdah; Tini Elyn Herlina; Yayuk Kustiningsih (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Hepatitis B infection is a clinical or pathological symptom characterized by various inflammations of the liver caused by Hepatitis B virus (HBV) infection (Siswanto, 2020) which can be transmitted through horizontal and vertical transmission. Horizontal transmission occurs from one person to another which can be transmitted through bodily fluids, sexual intercourse, and use of shared items. While vertical transmission occurs from pregnant women who are positive for the Hepatitis B virus to their fetuses, which can be transmitted through the placenta, during childbirth, and breast milk (Jalaluddin, 2020). This community service applies the research results of Safitri and Nurulhuda (2023) who obtained the results of HBsAg and Anti HBS examinations in pregnant women in Lok Buntar Village and Pematang Panjang Village in the Sungai Tabuk 1 Health Center area, Banjar Regency, 3 respondents were HBsAg reactive and 5 people were positive for Anti HBs. The problems experienced by partners include low levels of knowledge and understanding of clean and healthy living awareness to prevent transmission of hepatitis B, suboptimal empowerment of productive-age women and pregnant women, reactive hepatitis B test results are still found, and the unavailability of anti-HBS tests to determine the presence of hepatitis antibodies in pregnant women. The purpose of this community service activity is to educate and empower productive-age women and pregnant women who are active in the Bumil Sehati class activities. Cadres are equipped with knowledge about hepatitis B, how to prevent and treat hepatitis B infections and how to detect early occurrences of hepatitis B infections through physical examinations. This activity is carried out for 5 months from June to October 2024 with stages in the form of planning, implementation, evaluation and monitoring Evaluation to see an increase in knowledge about preventing hepatitis B in pregnant women, to see changes in healthy and clean living behavior in pregnant women. Availability of technical brochures for implementing healthy and clean living behavior to prevent transmission of Hepatitis B in pregnant women. From the results of the examination, 1 pregnant woman was found to be reactive to HBsAg and the results of the Anti-HBS examination were 3 people reactive. Handling and treatment of pregnant women who are positive for hepatitis are handed over to the midwives of the Community Health Center. The types of outputs produced in this PkM activity are 1) the formation of Bumil Sehati Cadres, 2) increased knowledge, 3) improved health of partners 4) Documentation in the form of videos and 5) Publication of the print media Radar Banjar. While additional outputs are in the form of cooperation between Poltekkes Kemenkes Banjarmasin and Bumil Sehati partners. Keyword: hepatitis B, anti HBs, pregnant woman